Divergent Mechanisms for PPARγ Agonism in Ameliorating Aging-Related Versus Cranial Irradiation-Induced Context Discrimination Deficits - Cortez, Ibdanelo; Denner, Larry; Dineley, Kelly T. (Frontiers in Aging Neuroscience, 2019)
ABSTRACT A major aspect of mammalian aging is the decline in functional competence of many self-renewing cell types, including adult-born neuronal precursors in a process termed neurogenesis. Adult neurogenesis is limited to specific brain regions in the mammalian brain, such as the subgranular zone (SGZ) of the hippocampus. Alterations in adult neurogenesis appear to be a common hallmark in different neurodegenerative diseases including Alzheimer’s disease (AD). We and others have shown that PPAR agonism improves cognition in preclinical models of AD as well as in several pilot clinical trials. Context discrimination is recognized as a cognitive task supported by proliferation and differentiation of adult-born neurons in the dentate gyrus of the hippocampus that we and others have previously shown declines with age. We therefore postulated that PPAR agonism would positively impact context discrimination in middle-aged mice via mechanisms that influence proliferation and differentiation of adult-born neurons arising from the SGZ. To achieve our objective, 8-months old mice were left untreated or treated with the FDA-approved PPAR agonist, rosiglitazone then tested for context discrimination learning and memory, followed by immunofluorescence evaluation of hippocampal subgranular zone cell proliferation and neuron survival. We found that PPAR agonism enhanced context discrimination performance in middle-aged mice concomitant with stimulated SGZ cell proliferation, but not new neuron survival. Focal cranial irradiation that destroys neurogenesis severely compromised context discrimination in middle-aged mice yet rosiglitazone treatment significantly improved cognitive performance through an anti-inflammatory mechanism and resurrection of the neurogenic niche. Thus, we have evidence for divergent mechanisms by which PPAR agonism impinges upon aging-related versus cranial irradiation-induced deficits in context discrimination learning and memory.